Quantum Aspects of Beam Physics 2003 2004
DOI: 10.1142/9789812702333_0017
|View full text |Cite
|
Sign up to set email alerts
|

Boiling the Vacuum With an X-Ray Free Electron Laser

Abstract: X-ray free electron lasers will be constructed in this decade, both at SLAC in the form of the so-called Linac Coherent Light Source as well as at DESY, where the so-called TESLA XFEL laboratory uses techniques developed for the design of the TeV energy superconducting electron-positron linear accelerator TESLA. Such X-ray lasers may allow also for high-field science applications by exploiting the possibility to focus their beams to a spot with a small radius, hopefully in the range of the laser wavelength. Al… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 25 publications
0
22
0
Order By: Relevance
“…These conditions are well satisfied at realistic optical as well as X-ray lasers [60,238,239]. The phenomenon of electron-positron pair production in alternating electric fields was studied in Refs.…”
Section: Phenomenology Of Pair Production In Alternating Fieldsmentioning
confidence: 94%
See 2 more Smart Citations
“…These conditions are well satisfied at realistic optical as well as X-ray lasers [60,238,239]. The phenomenon of electron-positron pair production in alternating electric fields was studied in Refs.…”
Section: Phenomenology Of Pair Production In Alternating Fieldsmentioning
confidence: 94%
“…We first briefly discuss the phenomenon of electron-positron pair production at the focus of an X-ray free electron laser, as given in the review articles [60,238,239]. In the early 1970's, the question was raised whether intense laser beams could be used to produce a very strong electric field by focusing the laser beam onto a small spot of size of the laser wavelength λ, so as to possibly study electron-positron pair production in vacuum [240,36].…”
Section: The Breit-wheeler Process In Laser Physicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Computing the effective action in nontrivial electric field configurations has been a challenging problem due to the vacuum instability; however, it has recently become one of the interesting subjects partly because direct tests of strong QED are possible in terrestrial experiments in the near future 4 and partly because strong QED can be applied to astrophysical objects with strong electromagnetic fields beyond the critical strength.…”
Section: Introductionmentioning
confidence: 99%
“…[2]). From an experimental view point, in the near future electromagnetic fields from X-ray free electron lasers from LCLS (Linac Coherent Light Source) at SLAC [3] and TESLA (TeV Energy Superconducting Linear Accelerator) at DESY [4] may attain a strength almost comparable to the critical value for electron-positron pair production, which will directly test strong QED [5]. Interestingly, astrophysical sources have been predicted and observed that can have electromagnetic fields greater than the critical strength.…”
Section: Introductionmentioning
confidence: 99%